Investigation Audit - Lilis Dwi Darma; Vebby Anggraeni Novita Sari Purba; Hafsyah Nabila; Tiar Vita Vera Br. Marpaung; Galih Supraja (Formosa Journal of Social Sciences (FJSS), 2024)
Investigative audits play a very important role in identifying violations and fraud that can harm an organization. This study aims to analyze the role of investigative audits in the follow-up of audit reports related to corruption. The investigative audit process carried out using appropriate techniques, such as reserve proof and existence of fraud, allows auditors to collect valid evidence that can be used as initial evidence in investigating corruption. Investigative audit findings that indicate violations must be followed up immediately through applicable procedures, involving related parties, such as law enforcement and internal oversight agencies. The results of this study indicate that investigative audits not only help reveal hidden facts, but also have a significant impact on decision-making regarding sanctions that can be given, either in the form of administrative, civil, or criminal sanctions. Thus, investigative audits have an important contribution in controlling and preventing corruption and maintaining organizational integrity